Analisis Penetapan Asal Usul Anak di Luar Nikah Perkara Nomor 52/Pdt.P/2025/PA.Prgi Pengadilan Agama Parigi - Musakip, Musakip; Marzuki, B.A; Thahir, Lukman. S. (Lembaga Teewan Journal Solutions, 2026)
This study aims to comprehensively analyze the legal basis, judicial considerations, and implications of the Determination of the Origin of a Child Born Outside of Valid Marriage, focusing on Case Number 52/Pdt.P/2025/PA.Prgi at the Parigi Religious Court. This study utilizes an empirical-juridical qualitative research method with a descriptive case-study approach. Primary data were gathered through structured interviews with the panel of judges and administrative registers at the Parigi Religious Court, supplemented by secondary data from Islamic legal jurisprudence, statutory laws, and the Constitutional Court Decision Number 46/PUU-VIII/2010. The findings indicate that the judges approved the determination of child origin based on continuous biological facts, testimonies, and humanitarian considerations to guarantee the child's basic rights. While strict classical fiqh restricts lineage (nasab) exclusively to a valid marriage contract, the court's modern adjudication balances formal normative constraints with progressive social reality. This decision successfully provides vital legal protection and civilian documentation certainty (identity cards and lineage recognition) for the child, ensuring the preservation of lineage and property rights (Hifz al-Nasl and Hifz al-Mal) within the framework of modern Indonesian Islamic Family Law.